2016
DOI: 10.1155/2016/9797410
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of miRNAs and Their Clinical Implication in Biliary Tract Cancer

Abstract: Biliary tract cancers are aggressive malignancies that include gallbladder cancer and tumors of intra- and extrahepatic ducts and have a poor prognosis. Surgical resection remains the main curative therapy. Nevertheless, numerous patients experience recurrence even after radical surgery. This scenario drives the research to identify biliary tract cancer biomarkers despite the limited progress that has been made. Recently, a large number of studies have demonstrated that deregulated expression of microRNAs is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…A large number of studies have highlighted the potential importance of circulating ncRNAs as diagnostic, prognostic, and/or predictive biomarkers in cancer, mainly microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). These molecules are remarkably stable as they are often incorporated into exosomes and microvesicles, thus providing resistance to RNase activity, extreme pH and multiple freeze-thaw cycles [ 62 63 , 65 67 ].…”
Section: Circulating Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have highlighted the potential importance of circulating ncRNAs as diagnostic, prognostic, and/or predictive biomarkers in cancer, mainly microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). These molecules are remarkably stable as they are often incorporated into exosomes and microvesicles, thus providing resistance to RNase activity, extreme pH and multiple freeze-thaw cycles [ 62 63 , 65 67 ].…”
Section: Circulating Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
“…Several studies also described associations between miRNA expression, H. pylori and EBV infection, which are well-known causes of GC [ 61 , 62 ]. For instance, Shiotani et al [ 73 ] observed an association between upregulated circulating miR-21 and miR-106b and H. pylori infection.…”
Section: Circulating Non-coding Rnas (Ncrnas)mentioning
confidence: 99%